THE EFFICACY OF INTERMITTENT PNEUMATIC COMPRESSION ASA SUBSTITUTE FOR MANUAL LYMPHATIC DRAINAGE IN COMPLETE DECONGESTIVE THERAPY IN THE TREATMENT OF BREAST CANCER RELATED LYMPHEDEMA - (:unkn) unknown (LYMPHOLOGY, 2019)
The aim of this study is to evaluate the efficacy of intermittent pneumatic compression (IPC) as a substitute for manual lymphatic drainage (MLD) in complete decongestive therapy (CDT) for treatment of advanced stages of breast cancer-related lymphedema. In this randomized, single-blind, controlled study, 46 patients with breast cancer-related lymphedema were divided into 2 groups. Both MLD with compression bandage (CB) group (n=24) and IPC with CB group (n=22) received treatment 3 days a week for 5 weeks. Home exercise program was also given to all patients. At the end of the 5th week, patients were treated with a daily 23-hour compression garment and home exercise routines. Assessments were taken at baseline, the fifth week, and the third month. Arm circumference was measured at 5 different areas, shoulder range of motion (ROM) was evaluated with a goniometer, pain, and tightness, and heaviness sensations were assessed with visual analog scale. Both groups had similar demographic and clinical characteristics (p < 0.05). There were no significant differences between groups and both groups showed significant improvement (p < 0.05) in the five measurement levels of the arm circumference at the fifth week and third month. Similarly, shoulder ROM, pain, tightness, and heaviness sensations improved in both groups (p < 0.05). Both MLD and IPC as a component of CDT were found successful at 5 weeks and 3 months without superiority to each other.
Keywords: lymphedema; complete decongestive therapy; intermittent pneumatic pump; lymphedema treatment; manual lymphatic drainage; ARM LYMPHEDEMA; PHYSIOTHERAPY